HuR post-transcriptionally regulates WEE1: Implications for the DNA damage response in pancreatic cancer cells - Lal, Shruti (Cancer Res, 2014)
HuR (ELAV1), an RNA binding protein abundant in cancer cells, primarily resides in the nucleus, but under specific stress (e.g., gemcitabine), HuR translocates to the cytoplasm where it tightly modulates the expression of mRNA survival cargo. Herein, we demonstrate for the first time that stressing pancreatic ductal adenocarcinoma (PDA) cells by treatment with DNA damaging anti-cancer agents (mitomycin C, oxaliplatin, cisplatin, carboplatin and a PARP-inhibitor) results in HuR’s translocation from the nucleus to the cytoplasm. Importantly, silencing HuR in PDA cells sensitized the cells to these agents, while overexpressing HuR caused resistance. HuR’s role in the efficacy of DNA damaging agents in PDA cells was, in part, attributed to the acute upregulation of WEE1 by HuR. WEE1, a mitotic inhibitor kinase, regulates the DNA damage repair pathway, and therapeutic inhibition of WEE1 in combination with chemotherapy is currently in early phase trials for the treatment of cancer. We validate WEE1 as a HuR target in vitro and in vivo by demonstrating: (1) direct binding of HuR to WEE1’s mRNA (a discrete 56-bp region residing in the 3’UTR), and (2) HuR siRNA silencing and overexpression directly affects the protein levels of WEE1, especially after DNA damage. HuR’s positive regulation of WEE1 increases γH2AX levels, induces Cdk1-phosphorylation and promotes cell cycle arrest at the G2/M transition. We describe a novel mechanism that PDA cells utilize to protect against DNA damage in which HuR post-transcriptionally regulates the expression and downstream function of WEE1 upon exposure to DNA damaging agents.